Normative approaches in making cultural quarters and assessment of creative industry parks in Shanghai - Zheng, Jane (Journal of Architecture and Urbanism, 2018)
This article aims to synthesize the principles of making cultural quarters in literature and test their applicability in creative industry parks in the Chinese context. Extant literature on creative industry parks in China lacks an evaluation instrument for evaluating the performance of creative industry parks. This research reviews normative theories regarding cultural quarter making and identifies three approaches, namely the area-based approach in cultural quarter design, architectural design principles (tailored to cultural quarters), and a comprehensive framework that comprises three dimensions, i.e., activity, built form, and meaning. These normative approaches were applied to evaluate the quality of creative industry parks that emerged in Shanghai in the recent decade. Qualitative research methods, including on-site reconnaissance, observation, and interview, were adopted. The former two approaches revealed good design practices in Shanghai’s creative industry parks. A systematic evaluation of the said parks through a comparative study suggests significant disparity in the dimensions of architectural design and place making. Additionally, indicators of state support for micro and small creative industry companies and arts funding are less applicable in Shanghai. These findings reveal the role of the private sector in constructing a diversified creative environment which was previously enshrined by the state. With these outcomes, this research partially endorses the value of the normative theories to guide the practice of making and evaluating cultural quarters in the Chinese context.